2003
DOI: 10.1086/375827
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Membrane Protein (PMP) 20 and PMP 21 ofChlamydia pneumoniaeInduce Proinflammatory Mediators in Human Endothelial Cells In Vitro by Activation of the Nuclear Factor‐κB Pathway

Abstract: We tested whether polymorphic membrane proteins (PMPs) of Chlamydia pneumoniae might play a role in triggering an inflammatory response in human endothelial cells. Of 15 purified, recombinant chlamydial PMPs tested, 2 (PMP 20 and PMP 21) dose-dependently increased the production of the inflammatory mediators interleukin (IL)-6 and monocyte chemoattractant protein-1 (MCP-1), in cultured human endothelial cells; production of IL-8 was also increased. When endothelial cells were infected by live C. pneumoniae, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…Moreover, examination of the role of the POMPs in triggering an immune response recently demonstrated that Pmp20 and Pmp21 from C. pneumoniae could increase the production of the inflammatory mediators IL-6, IL-8 and monocyte chemoattractant protein 1 in a dose-dependent fashion in cultured human endothelial cells. Furthermore, this induction was due to the activation of the nuclear factor B pathway (353). It was suggested that by interaction of the POMPs with the endothelium, the POMPs contribute to vascular injury and thus to the development and progression of atherosclerotic lesions, which are associated with infection by several organisms from the Chlamydiaceae.…”
Section: Cluster 7: Chlamydial Autotransportersmentioning
confidence: 99%
“…Moreover, examination of the role of the POMPs in triggering an immune response recently demonstrated that Pmp20 and Pmp21 from C. pneumoniae could increase the production of the inflammatory mediators IL-6, IL-8 and monocyte chemoattractant protein 1 in a dose-dependent fashion in cultured human endothelial cells. Furthermore, this induction was due to the activation of the nuclear factor B pathway (353). It was suggested that by interaction of the POMPs with the endothelium, the POMPs contribute to vascular injury and thus to the development and progression of atherosclerotic lesions, which are associated with infection by several organisms from the Chlamydiaceae.…”
Section: Cluster 7: Chlamydial Autotransportersmentioning
confidence: 99%
“…Besides the serologically defined and molecularly characterized chlamydial Ags recognized during human infection (6,24,25), recent advances in chlamydial genomics have predicted several immunogenic proteins (26 -28) that may serve as potential vaccine candidates. The most prominent among these to date include the polymorphic OMPs (29) (30,31), the conserved PorB family of membrane proteins (32)(33)(34), and the ADP/ATP translocase of Chlamydia pneumoniae (26,27).…”
Section: G Enital Infection With the Obligate Intracellular Bacteriummentioning
confidence: 99%
“…Furthermore, recombinant C. pneumoniae PmpD has been suggested to function as an adhesin capable of inducing proinflammatory cytokine production (35,52). Nothing is known about the native structure of C. trachomatis PmpD or the potential significance of its structure to chlamydial pathogenesis.…”
mentioning
confidence: 99%